Enriching Vocabulary by Using Alphabet Game at Group Discussion in Teaching ENGLISH for the Tenth Grade of SMKN 1 Labang - Ardiyansah (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2018)
Vocabulary is the most important component in language acquisition. Vocabulary is one of the fundamental factors that make it possible for a person to speak the language. This study are different form in pronunciation and spelling, the low level of students in memorizing the words their boredom in learning, the lack of media and vocabulary. Most of the students have good responses for the teaching and learning process. They liked and felt enthusiastic in following this lesson. The students agree when the teacher conducted the lesson using alphabet game to enrich vocabulary. Beside the students also felt that their English is becoming better than before especially in analyzing kinds of noun